2023
DOI: 10.3390/nu15224805
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Support Resilience of the Oral Microbiota during Resolution after Experimental Gingivitis—A Randomized, Double-Blinded, Placebo-Controlled Trial

Christine Lundtorp Olsen,
Laura Massarenti,
Vincent Frederik Dahl Vendius
et al.

Abstract: The present study aims to test whether probiotics protect against experimental gingivitis incited by 14 days of oral hygiene neglect and/or subsequently support the restoration of oral homeostasis. Eighty systemically and orally healthy participants refrained from oral hygiene procedures for 14 days, followed by 14 days with regular oral hygiene procedures. Additionally, participants consumed either probiotics (n = 40) or placebo (n = 40) throughout the trial. At baseline, day 14, and day 28, supragingival pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The use of probiotics as adjuvant treatment in different diseases seems promising. Several clinical trials reported improvement in halitosis, oral health, and related quality of life in subjects supplemented with different formulation of probiotics [ 65 , 66 , 67 , 68 , 69 ]. Moreover, many beneficial effects have been already demonstrated in the rebalance of the gut microbiota and also systemically [ 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of probiotics as adjuvant treatment in different diseases seems promising. Several clinical trials reported improvement in halitosis, oral health, and related quality of life in subjects supplemented with different formulation of probiotics [ 65 , 66 , 67 , 68 , 69 ]. Moreover, many beneficial effects have been already demonstrated in the rebalance of the gut microbiota and also systemically [ 70 , 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few RCTs have tested the microbiological effect of probiotics in the treatment of gingivitis ( [73][74][75][76][77], Table 1). In gingivitis, different Lactobacillus species, including L. rhamnosus, L. curvatus, L. plantarum, L. brevis, and L. reuteri, have been delivered as tablets [74][75][76][77] or lozenges [73], either during experimental gingivitis [73,76] or as treatment of established gingivitis [74,75,77].…”
Section: Gingivitismentioning
confidence: 99%
“…Few RCTs have tested the microbiological effect of probiotics in the treatment of gingivitis ( [73][74][75][76][77], Table 1). In gingivitis, different Lactobacillus species, including L. rhamnosus, L. curvatus, L. plantarum, L. brevis, and L. reuteri, have been delivered as tablets [74][75][76][77] or lozenges [73], either during experimental gingivitis [73,76] or as treatment of established gingivitis [74,75,77]. The microbiological effect has been evaluated in supragingival plaque [73,76], saliva [74], subgingival plaque [75], and simultaneously in subgingival plaque and saliva samples [77], using 16S sequencing [73,74], qPCR [75,77], and DNA-DNA checkerboard [76] immediately after probiotic consumption for 28 days to 8 weeks.…”
Section: Gingivitismentioning
confidence: 99%
See 2 more Smart Citations